(untitled) (Journal of the College of Basic Education, 2022)
The present study was Conducted to evaluate the effect of amixture of three species of arbuscular mycorrhizal fungi ( Glomus etunicatum , G. leptotichum and Rhizophagus intraradices ) in Influence on the percentage of the components of NPK and protein of tomato leaves and roots infected with Fusarium oxysporum f.sp. Lycopersici wich cause Fusarial wilt disease , planted for 8 weeks in the presence of the organic matter ( peatmose) , using pot cultures in aplastic green house , Results indicated significant increase in the percentage of the elements of NK and protein of tomato leaves and roots In the control treatment (C), While the percentage of the element P was after infection with the pathogen 4 weaks after mycorrhizal colonization in all treatments ( single , dual and trial interactions) . on the other hand mycorrhizal colonization of the leaves and roots in the presence of organic matter and pathogen after 4 weaks of pathogen infection resulted in significant increase in the percentage of the elements of NK and protein of leaves and roots in all treatment ( single , dual and trial interaction ) . The treatment ( M+ × O+ x C) Showed the highest Percentage followed by the trial ( M+ × 4W+ x O+) , The P element was the highest in the treatment of trial interaction ( M+ × 4W+ x O+) followed by the dual ( M+ x 4W+ ), whereas the lowest decline in the ratio of the elements and protein for all treatments was shown at the time of plantation ( OW+ ) in the presence of the pathogen . Overall, the study showed an increase in the percentage of the elements of NPK and protein in the leaves than the roots.